通过使用完成平方的方法,分解以下每个二次多项式
问题1. p 2 + 6p + 8
解决方案:
p2 + 6p + 8
= p2 + 2 x p x 3 + 32 – 32 + 8 (completing the square)
= (p2 + 6p + 32) – 1
= (p + 3)2 – 1
= (p + 3)2 – (1)2 { ∵ a2 + b2 = (a + b) (a – b)}
= (p + 3 + 1) (p + 3 – 1)
= (p + 4) (p + 2)
问题2 Q 2 – 10Q + 21
解决方案:
q2 – 10q + 21
= (q)2 – 2 x q x 5 + (5)2 – (5)2 + 21 (completing the square)
= (q)2 – 2 x q x 5 + (5)2 – 25+ 21
= (q)2 – 2 x q x 5 + (5)2 – 25 +21
= (q)2 – 2 x q x 5 + (5)2 – 4
= (q – 5)2 – (2) {∵ a2 – b2 = (a + b) (a – b)}
= (q – 5 + 2) (q – 5 – 2)
=(q – 3) (q – 7)
问题3. 4y 2 + 12y + 5
解决方案:
4y2 + 12y + 5
= (2y)2 + 2 x 2y x 3 + (3)2 – (3)2 + 5 (completing the square)
= (2y + 3)2 – 9 + 5
= (2y + 3)2 – 4
= (2y + 3)2 – (2)2 {∵ a2 – b2 = (a + b) (a – b)}
= (2y + 3 + 2) (2y + 3 – 2)
= (2y + 5) (2y + 1)
问题4. p 2 + 6p – 16
解决方案:
p2 + 6p – 16
= (p)2 + 2 x p x 3 + (3)2 – (3)2 – 16 (completing the square)
= (p)2 + 2 x p x 3 + (3)2 – 9 – 16
= (p + 3)2 – 25
= (p + 3)2 – (5)2 {∵ a2 – b2 = {a + b) (a – b)}
= (p + 3 + 5)(p + 3 – 5)
= (p + 8) (p – 2)
问题5. x 2 + 12x + 20
解决方案:
x2 + 12x + 20
= (x)2 + 2 x x x 6 + (6)2 – (6)2 + 20 (completing the square)
= (x)2 + 2 x x x 6 + (6)2 -36 + 20
= (x + 6)2 -16
= (x + 6)2 – (4)2 {∵ a2 – b2 = (a + b) (a – b)}
= (x + 6 + 4) (x + 6 – 4)
= (x + 10) (x + 2)
问题6. a 2 – 14a – 51
解决方案:
a2 – 14a – 51
= (a)2 – 2 x a x 7 + (7)2 – (7)2 – 51 (completing the square)
= (a)2 – 2 x a x 7 + (7)2 – 49 – 51
= (a – 7)2 – 100
= (a – 7)2 – (10)2 {∵ a2 – b2 = (a + b) (a – b)}
= (a – 7 + 10) (a – 7 – 10)
= (a + 3) (a – 17)
问题7. a 2 + 2a – 3
解决方案:
a2 + 2a – 3
= (a)2 + 2 x a x 1 + (1)2 – (1)2 – 3 (completing the square)
= (a)2 + 2 x a x 1 + (1)2 – 1 – 3
= (a + 1)2 – 4
= (a + 1)2 – (2)2 {∵ a2 – b2 = (a + b) (a – b)}
= (a + 1 + 2) (a + 1 – 2)
= (a + 3) (a – 1)
问题8. 4x 2 – 12x + 5
解决方案:
4x2 – 12x + 5
= (2x)2 – 2 x 2x x 3 + (3)2 – (3)2 + 5 (completing the square)
= (2x)2 – 2 x 2x x 3 + (3)2 – 9 + 5
= (2x – 3)2 – 4
= (2x – 3)2 – (2)2 {∵ a2 – b2 = (a + b) (a – b)}
= (2x – 3 + 2) (2x – 3 – 2)
= (2x – 1) (2x – 5)
问题9. y 2 – 7y + 12
解决方案:
y2 – 7y + 12
= (y)2 – 2 × y × 7/2 + (7/2)2 – (7/2)2 + 12 (completing the square)
= (y)2 – 2 × y × 7/2 + 49/4 – 49/4 + 12
= (y – 7/2)2 – (49 – 48)/4
= (y – 7/2)2 – 1/4
= (y – 7/2)2 – (1/2)2 {∵ a2 – b2 = (a + b) (a – b)}
= (y – 7/2 + 1/2) (y – 7/2 – 1/2)
= (y – 6/2) (y – 8/2)
= (y – 3) (y – 4)
问题10. z 2 – 4z -12
解决方案:
z2 – 4z – 12
= (z)2 – 2 x z x 2 + (2)2 – (2)2 – 12 (completing the square)
= (z)2 – 2 x z x 2 + (2)2 – 4 – 12
= (z – 2)2 – 16
= (z – 2)2– (4)2 {∵ a2 – b2 = (a + b) (a – b)}
= (z – 2 + 4) (z – 2 – 4)
= (z + 2)(z – 6)